The semiotic analysis of the collisions between dominant myths and counter-myths in three Indonesian horror movies - Muhamad Gibraltar; Hamedi Mohd Adnan; Mohamad Saleeh Rahamad (Penerbit Universiti Kebangsaan Malaysia, 2023)
Indonesia has a new sociological trend about dialectical reconciliations between counter-myths and dominant myths and vice versa (macro-level), and it is reflected semiotically in scenes in three Indonesian horror movies, like Pengabdi Setan, Suzanna Bernapas Dalam Kubur, and Sebelum Iblis Menjemput (micro-level). Sometimes the scenes (in horror movies) contain the collisions between counter-myths and dominant myths (and vice versa), or the scenes show the dialectical reconciliations between both myths. Therefore, this study aims to analyse how the collisions between dominant myths and counter-myths and vice versa are described in three Indonesian horror movies. Sociologically, the semiotic examination shows the trend of the last two types of dialectical reconciliations between Islamic teachings and adultery and between Islamic teachings and corrupt practices, since the first two reconciliations have been explained in another manuscript. Also, there are four motives why people adopt counter-myths, like (1) the treasure (harta), (2) the political position (takhta), (3) the romance (asmara), and (4) the sexual pleasure (kesenangan seksual). In contrast, there are two motives why people go back to re-adopting dominant myths, like (1) regret (penyesalan) and (2) safety (keamanan). Moreover, the study discusses the draft of the new Postmillennial Gothic, which rehabilitates and beautifies Indonesian demonic characters to fight criminals who practice the dialectical reconciliation between dominant myth and counter-myth. Finally, it is possible to apply this idea in Indonesia because there are cultural and sociological situations that support its implementation.